The semantics of colors in Arabic and English poetry: A comparative study of Al-Mutanabbi’s poems and Shakespeare’s sonnets - Aldaw, Hassan Musa Mohammad (Research Journal in Advanced Humanities, 2023)
The study aimed at interpreting the concept of color across cultures with reference to Arabic and English. It investigated the semantic denotation of colors by the type of emotions conveyed in the poems of Al-Mutanabbi and the sonnets of Shakespeare with respect to the symbolic meaning. The study focused on the lines in which color appeared in a symbolic sense. The poetic evidence for color existence in the poems were collected. The study followed the descriptive-analytical approach to investigate and clarify the aspects of the significance of colors and their denotations. The study revealed that studying the semantic denotation of colors could be a confusing subject even within the one culture, as some colors had different associations in different occasions. The two poets sometimes used the same color to convey different meanings, and sometimes more than one color were used in the same poetic line or verse to reflect the inner-self of the poets. Color denotations were determined according to personal or public intuition and culture but there were no clear-cut linguistic universals for the symbolic use of colors. The study recommended that more studies should be conducted on the denotation of colors to reach a semantic universal concept.